A systematic literature review of risk management in the Islamic banking system: research agenda and future directions - Hossain, MD Alamgir; Rosman, Romzie; Jahan, Nasrin; Afroz, Shahana; Afroza, Kaniz (Research and Scientific Innovation Society, 2025)
In the evolving landscape of global finance, effective risk management within the Islamic banking system has garnered significant attention. This paper presents a systematic literature review that explores the research agenda and future directions in risk management practices specific to Islamic banking. Utilizing the PRISMA framework, a total of 43 relevant articles published between 2004 and 2024 were meticulously selected from the Scopus database and analyzed. The review highlights a diverse range of methodologies, with 34 articles employing quantitative approaches, 7 utilizing qualitative methods, and 2 incorporating mixed methods. The findings indicate a strong predominance of quantitative research, suggesting a critical need for further exploration of qualitative and mixed-method studies to achieve a more comprehensive understanding of risk management in Islamic banking. Additionally, the analysis identifies a significant gap in the literature regarding innovative risk management strategies that align with the unique principles of Islamic finance. This review serves as a vital resource for researchers, practitioners, and policymakers aiming to enhance their understanding of risk management within the Islamic banking sector. By synthesizing existing literature and pinpointing areas for future research, this paper contributes to the ongoing discourse on effective risk management in Islamic finance.